Rozwój społecznej odpowiedzialności biznesu na Ukrainie - Polinkevych, Oksana M.; Kolosok, Andrii M. (Polskie Towarzystwo Ekonomiczne Oddział w Poznaniu, 2022)
The authors consider the issue of social responsibility of business and its compliance with European practice. The legal regulation of joint stock companies in Ukraine is outlined, the disadvantages and advantages of the existence of joint stock companies in Ukraine are identified. The analysis of non-financial reporting of joint-stock companies in Ukraine is carried out, the activity of Ukrainian enterprises is characterized.
Keywords: social responsibility; Volyn; non-financial sector; joint-stock companies; securities market